Asuhan Keperawatan Pada Keluarga Tn. S dengan Masalah Utama Pada Ny. R di Sanggrahan, Krajan, Gatak, Sukoharjo - Lestari, Retno Dwi, Supratman, Ph.D (2015)
FAMILY NURSING CARE OF MR. S FAMILY WITH MAIN PROBLEM TUBERCULOSIS FOR MRS. R IN SANGGRAHAN, KRAJAN, GATAK, SUKOHARJO (Retno Dwi Lestari, 2015, 67 pages) ABSTRACT Background: Tuberkulosis an infection that attacks parenkim of the lungs caused by Mycobacterium tuberculosis. This illness is always becoming problem in the world, moreover in Indonesia the numbers of death due to tuberculosis is rising because the risk of contagion is very high. Based on Indonesian Health Departement in 2010, 289 from 100.000 people were die because of this infection disease. Objective: Knowing about the study of nursing care with pulmonary TB and able to apply it in patiens with pulmonary TB. Method: The research included assessement, diagnosis, intervention, implementation and evaluation of nursing.. Result: After assasement, appears two problems, namely, less knowledge and infection risk. In the implementation of the most appropriate intervention has done that has been created. Conclusion: After 3 days intervention, the problem of lacking knowledge is resolved in part and need further treatment primarily by family, while the problem of the risk of contagion is not resolved because the economics of family low. Keywords: Family nursing care, tuberculosis, the risk of transmission.